Collateral sprouting axons of end-to-side nerve coaptation in the avulsion of ventral branches of the C5-C6 spinal nerves in the brachial plexus - Reichert, Paweł; Kiełbowicz, Zdzisław; Dzięgiel, Piotr; Puła, Bartosz; Kuryszko, Jan; Wrzosek, Marcin; Kiełbowicz, Maciej; Gosk, Jerzy (Folia Neuropathologica, 2015)
Introduction: This study assessed the collateral sprouting in avulsion of the ventral branches of the C5 and C6 spinal nerves treated by coaptation of these nerves to the C7 spinal nerve on the brachial plexus of rabbits. Material and methods: Thirty-six New Zealand rabbits were randomly divided into four groups: end-to-side coaptation (ESN) (n = 12), side-to-side coaptation (SSN) (n = 12), direct neurorrhaphy (end-to-end) (EEN) (n = 6) and no coaptation (n = 6). The operations were performed on the left brachial plexus. The contralateral, non-operated right brachial plexi were used as the control group. The groups were compared using morphological, electrophysiological and behavioral methods. The follow-up duration was 20 weeks. Results: Significant differences were observed in all parameters when the experimental groups were compared with the control group and the no coaptation group. The histology of axonal regeneration after ESN, but not after SSN, was comparable to that after EEN. There were no significant differences in the electrophysiological, behavioral assessment or G-ratio parameters between the ESN and EEN groups. There were significant differences in the behavioral assessment, G-ratio and the histomorphometric parameters between the SSN and EEN groups, which disagreed with the electrophysiological results. Sensory axon collateral sprouting was more rapid than motor axon collateral sprouting. Conclusions : The electrophysiological, histomorphometric and behavioral results obtained using end-to-side coaptation of ventral branches of the C5 and C6 spinal nerves to the C7 spinal nerve in the brachial plexi of rabbits confirm the occurrence of collateral sprouting at this level. After further research is performed to confirm the results of this study, end-to-side coaptation might emerge as an alternative method in the treatment of brachial plexus avulsion.